Animal and Plant Protein Food Sources in Indonesia Differ Across Socio-Demographic Groups: Socio-Cultural Research in Protein Transition in Indonesia and Malaysia - Khusun, Helda; Februhartanty, Judhiastuty; Anggraini, Roselynne; Mognard, Elise; Alem, Yasmine; Noor, Mohd Ismail; Karim, Norimah; Laporte, Cyrille; Poulain, Jean-Pierre; Monsivais, Pablo; Drewnowski, Adam (Frontiers in Nutrition, 2022)
Background: Plant-based diets in lower-income countries are often associated with inadequate protein nutrition and adverse health outcomes. Objective: To examine the diversity of protein food sources, animal and plant, across diverse sociodemographic groups in Indonesia as compared to Malaysia. Design: The SCRiPT (Socio Cultural Research in Protein Transition) study was based on population-based samples recruited in Indonesia (N=1665) and in Malaysia (N=1604). Data from 24h in-person dietary recalls in each country were used to construct frequency counts of protein sources by food group. Protein sources were defined as fish, poultry, red meat (beef, pork, and mutton), eggs, dairy, and plants (cereals, pulses, tubers). Percent reported frequencies for animal and plant proteins were compared across socio-demographic strata and by country. Analyses were based on one-way Anovas and general linear model regressions adjusting for covariates. Results: Animal protein frequency counts were 34% of total in Indonesia but 50% in Malaysia. Higher reported consumption frequencies for poultry and red meat in both countries were associated with urban living, greater modernization and higher socioeconomic status, with stronger social gradients observed in Indonesia. Reported fish consumption was higher in Indonesia than in Malaysia. Fish was more likely to be listed by rural island populations in Indonesia and was associated with lower education and incomes. Consumption frequencies for plant-based proteins were associated with lower socioeconomic status in Indonesia and in Malaysia. Conclusions: More affluent groups in both countries reported higher frequencies for meat, eggs and dairy as opposed to fish, Greater economic development in SE Asia is associated with more animal protein, particularly from poultry, which may displace fish, the traditional source of high quality protein for the region.